2021
DOI: 10.1177/1362361321997284
|View full text |Cite
|
Sign up to set email alerts
|

Associations between social camouflaging and internalizing symptoms in autistic and non-autistic adolescents

Abstract: Autistic individuals experience higher rates of psychiatric comorbidities than their peers. Camouflaging, the process through which individuals hide autistic traits, can be detrimental to mental health. This may be particularly true for autistic females, although research on sex differences in the relationship between camouflaging and mental health has focused on adults. The purpose of this study was to extend previous research on camouflaging and mental health through examining age, sex, autism diagnosis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 55 publications
4
36
0
Order By: Relevance
“…These results replicate previous findings that non-autistic people engage in camouflaging 4,14,17 and that camouflaging in non-autistic people is related to social competence 15 . Further, these results are consistent with previous studies indicating that camouflaging is associated with internalizing behaviours among autistic and non-autistic adolescents 17 and autistic adults 18 . The current research extends these findings in a sample of non-autistic adults, taking into consideration their social competence.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results replicate previous findings that non-autistic people engage in camouflaging 4,14,17 and that camouflaging in non-autistic people is related to social competence 15 . Further, these results are consistent with previous studies indicating that camouflaging is associated with internalizing behaviours among autistic and non-autistic adolescents 17 and autistic adults 18 . The current research extends these findings in a sample of non-autistic adults, taking into consideration their social competence.…”
Section: Discussionsupporting
confidence: 90%
“…For example, autistic adults have reported that camouflaging is necessary to procure and maintain employment 3 . However, despite the possible advantages, there is emerging evidence that camouflaging may be a risk factor for internalizing behaviour 17,18 . Internalizing behaviour is a broad category of psychological behaviours that are directed inwards and create psychological distress within the individual, including anxiety and depression 19 .…”
Section: Camouflaging and Internalizing Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 provides an overview of participant characteristics for participants with autism diagnoses or high autistic traits. There were four sets of studies in which samples were partially or fully duplicated (Hull et al, 2019;Hull, Lai, et al, 2020;Hull, Levy, et al, 2021;Jorgenson et al, 2020;Bernardin et al, 2021;Lai et al, 2017Lai et al, , 2019Livingston, Shah, & Happé, 2019;Livingston et al, 2020). In these instances, only information from one study (the study with the largest N) was counted when calculating aggregated participant characteristics.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…It has been suggested that ASD might both share a common etiopathological root with other disorders and be itself the ground where other disorders flourish [ 8 , 9 ]. The role of ASD as a psychopathological risk factor is confirmed by a number of studies, especially when focusing on the high level of distress in everyday life due to the lack of interpersonal and communication skills and leading to anxiety, depression, trauma/stress-related symptoms and suicidal thoughts [ 10 , 11 , 12 , 13 , 14 ]. This might be especially critical for mild forms of ASD, which often remain unknown through childhood and make their first appearance during adolescence or adulthood, when social demands exceed the individual coping ability [ 1 ].…”
Section: Introductionmentioning
confidence: 99%